Analisis Penggunaan Buku Tematik Pada Kurikulum Merdeka dalam Meningkatkan Pemahaman Konsep Siswa di SDN Sukamaju - Maisya Syifa Ramadina; Dwi Undayasari (DPPM Universitas Pelita Bangsa, 2025)
The transition from the 2013 Curriculum to the Merdeka Curriculum has precipitated modifications in the utilization of thematic books in elementary schools. The objective of this study is to analyze the implementation of the Merdeka Curriculum thematic book and its impact on students' conceptual understanding at SDN Sukamaju. The methodological approach employed is descriptive qualitative, encompassing teacher interviews and questionnaires administered to sixth-grade students. The findings indicate that the Merdeka Curriculum thematic book boasts visual advantages and a plethora of activities; however, it falls short in its capacity to provide comprehensive support for conceptual understanding, particularly in the upper grades. Teachers have expressed concerns regarding the book's completeness, leading to the utilization of supplementary resources. Concurrently, students have encountered challenges in comprehending the concepts presented. The study's findings suggest that enhancing the book's content and providing teacher guidance would render it more suitable for students' cognitive development stage.